Finite element analysis of the failure of high-strength steel pipelines containing group corrosion defects. (June 2022) - Zhou, Rui; Gu, Xiaoting; Bi, Shubo; Wang, Jian
Highlights: A finite element model of high-strength steel pipe containing group corrosion defects is made. Failure mechanism is explored to derive the failure law of X80 pipes. Size of the deepest defect depth in the corrosion group mainly affects failure pressure of pipelines. Deepest defect length and inter-group axial spacing are secondary factors affecting the failure pressure. Abstract: Corrosion defects in steel pipes can lead to pipeline failure, and such failures can have severe impacts; thus, developing appropriate corrosion mitigation schemes to prevent them can be beneficial. To this end, the influences of variables such as the depth, length, and group spacing of corrosion defects on the failure of X80 steel pipes containing group corrosion defects were analysed in this study. Abaqus, a simulation software, was used for non-linear finite element analyses, and 52 groups corresponding to corrosions under different geometric factors were prepared. Furthermore, a pipeline failure pressure prediction model was established using 138 sets of simulations to determine the maximum von Mises stresses of pipelines subjected to internal pressures under different working conditions. Actual blast test data and error comparisons with various existing evaluation standards were conducted to verify the accuracy of the proposed model. The results revealed that an increase in the internal pressure and the changes in the depth, length, and group spacing of group corrosion defects impact the maximum von Mises stress in the pipe. Among the group corrosion defects considered, the depth of the deepest defect was found to be the most critical factor in determining the form of damage and the failure pressure of pipes containing corrosion defects. The length of corrosion defects and the axial spacing between groups of defects were found to be the secondary factors that affect the failure pressure. In an actual pipeline, group corrosion defects are expected to cause a reduction in the wall thickness and, thus, pose a threat to safety, an issue that warrants substantial attention. The results of this work can serve as a reference for assessing the failure of X80 steel pipelines containing group corrosion defects.